Oczyszczanie gnojowicy metodą aerobową termofilową - Raczyk, Andrzej; Cichosz, Natalia; Jeszka, Piotr; Zgoła, Lidia; Kołaczkowski, Stanisław T. (Zielona Góra: Uniwersytet Zielonogórski)
Investigations are made with aerobic thermophilic treatment of hoge manure. A diminishing of BOD - load 2,5 ... 5,8 kg O2/m3 ? d. is obtained. This method in technical rang may be employed.
Keywords: metoda aerobowa termofilowa